2018
DOI: 10.1007/s11005-018-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-singular space-times with a negative cosmological constant: V. Boson stars

Abstract: We prove existence of large families of solutions of Einsteincomplex scalar field equations with a negative cosmological constant, with a stationary or static metric and a time-periodic complex scalar field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is clear that the method opens further possibilities, which remain to be explored. For example, the technique is used in [17] to construct boson star solutions.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the method opens further possibilities, which remain to be explored. For example, the technique is used in [17] to construct boson star solutions.…”
Section: Introductionmentioning
confidence: 99%
“…While this doesn't seem to agree with some observations which show a tiny positive value of Λ (≈ 10 −123 ) [84], the negative value of Λ can also fit a large data set and solve the eternal acceleration problem [85]. The negative Λ approach has been studied by many authors [85][86][87][88][89][90]. The negative Λ is also supported in the framework of the AdS/CFT correspondence [91].…”
Section: Cosmological Equations and Solutionsmentioning
confidence: 81%
“…While observations suggest a very small positive Λ (Perlmutter et al 1999;Tonry et al 2003;Clocchiatti et al 2006), negative Λ is also possible by other observations and can present a solution to the eternal acceleration problem which has been shown to be a consequence of the positive Λ (Vincenzo et al 2008). The negative Λ approach has been studied by many authors (Cardenas et al 2003;Grande et al 2006;Gong and Wang 2007;Vincenzo et al 2008;Prokopec 2011;Landry et al 2012;Maeda and Ohta 2014;Baier et al 2015;Ahmed and Alamri 2018;ChruÅ›ciel et al 2018), and it is shown to be supported by the AdS/CFT correspondence (Aharony et al 2000). The possibility of observationally viable FRW cosmologies with negative Λ has been shown by (Prokopec 2011).…”
Section: Solutionsmentioning
confidence: 95%
“…A stable de Sitter solution with negative Λ has been found in Gauss-Bonnet gravity by (Maeda and Ohta 2014). Solutions of Einsteincomplex scalar field equations with negative Λ has been presented in (ChruÅ›ciel et al 2018). So, the current solution with negative Λ has a solid theoretical and observational ground.…”
Section: Solutionsmentioning
confidence: 96%